Intrathecal Fibrinolysis for Aneurysmal Subarachnoid Hemorrhage: Evidence From Randomized Controlled Trials and Cohort Studies - Lu, Xiaocheng; Ji, Chengyuan; Wu, Jiang; You, Wanchun; Wang, Wei; Wang, Zhong; Chen, Gang (Frontiers in Neurology, 2019)
Background: The role of intrathecal fibrinolysis for the treatment of patients with aneurysmal subarachnoid hemorrhage (aSAH) has been widely investigated, whereas the results have been contradictory. Here, we conducted a meta-analysis to evaluate the safety and efficacy of intrathecal (intracisternal or intraventricular) fibrinolysis on aSAH. Methods: PubMed, Web of Science, Embase, Medline and Cochrane library databases were searched up to February 01, 2019. The outcomes analyzed were neurological recovery, delayed ischemic neurological deficit (DIND), mortality, as well as the incidence of chronic hydrocephalus and hemorrhage. Results: A total of 21 studies comprising 1373 patients were analyzed, including 9 randomized controlled trials (RCTs) and 12 non-RCTs. The results showed that intracisternal fibrinolysis significantly decreased poor neurological outcomes (RR=0.62, 95%CI=0.50-0.76, p<0.001) and reduced the incidence of DIND (RR=0.52, 95%CI=0.41-0.65, p<0.001), chronic hydrocephalus (RR=0.59, 95%CI=0.42-0.82, p=0.002) and mortality (RR=0.58, 95%CI=0.37, 0.93, p=0.02). There was no significant difference in the occurrence of hemorrhage complication. Moreover, the results Egger’s test and Begg’s funnel plot did not show any evidence of publication bias. Conclusions: The current evidence suggested that intracisternal fibrinolysis had beneficial effects on the clinical outcomes of patients with aSAH. However, further well-designed randomized trials are needed to confirm the efficacy and safety of intracisternal fibrinolysis for the treatment of aSAH.